Vol. 10 (1-2):100-102 Bio-Efficacy of different insecticides against Custard apple mealy bug, (Maconellicocus hirsutus) (Indian Journal of Arid Horticulture, 2025)
Custard apple or sugar apple (Annona squamosa L) is considered as the new super fruit of 21" century belonging to the family Annonaceae. It is one of the important minor fruit crops in India, commonly known as sitaphal, sita palam, sharifa, sita pazham, sita phalmu, katal, ata and sweet sop depending upon the region. Fruits can be called as a delicacy of dry region due to its very sweet delicate flesh and are rich in carbohydrate mainly in the form of sugar, protein, calcium, phosphorus and iron. It is grown throughout the plains of India except temperate region. The major custard apple growing states are Maharashtra, Gujarat, Andhra Pradesh, Uttar Pradesh, Madhya Pradesh, Bihar, Assam, Rajasthan, Orissa and Tamil Nadu. Approximately 55,000 hectares are dedicated to custard apple cultivation (Anonymous, 2014). In Maharashtra, custard apple is grown in Pune, Beed, Aurangabad, Nanded, Dhule, Jalgaon, Nandurbar, Osmanabad, Latur, Ahmednagar, Solapur, Bhandara and Wardha districts. Balaghat hills of Marathwada are famous for natural occurrence of custard apple plantation. The fruit tolerates a variety of conditions from saline soils to droughts.
Keywords: Annona squamosa L; Annonaceae; occurrence; Planococcus citri; Maconellicoccus